Conclusion [in The political economy of food system transformation: Pathways to progress in a polarized world] - Resnick, Danielle; Swinnen, Johan (International Food Policy Research Institute, 2023)
While the need for policy reforms to generate more equitable, healthier, and sustainable food systems increasingly is acknowledged by policymakers and the public, the political economy dynamics to achieve this will remain sizeable in the years to come. This is particularly true given the range of polarizing factors affecting decisions over the food system at domestic and international levels—from debates over values and (mis)information, to concerns over food self-sufficiency, corporate influence, and human rights. By prioritizing political economy issues in the food and agricultural policy arena, this volume has aimed to delineate the range of incentive structures, mobilizational forces, policy designs, and implementation concerns that either propel or derail reforms. This chapter summarizes key messages from the volume, highlighting promising options to achieve food system transformation as well as areas that are likely to be more intractable.